Ensino de matemática na EJA: relações entre os conhecimentos do mundo do trabalho e os escolares - Capeleti, Everton Vitola (2023)
The dissertation referred to in this text presents the teaching of Mathematics in Youth and Adult Education (EJA) as a problem, particularly the difficulty of students in this modality in establishing relationships between mathematical concepts acquired spontaneously in the experiential world, including in their work activities, and the typical scientific concepts of the school. The study suggests that the production of short videos by students, reporting contextualized situations from their daily work and which intrinsically use mathematical knowledge, may prove to be relevant to the acquisition of scientific knowledge characteristic of the school. This understanding leads to the central research question: What is the didactic relevance of a teaching sequence aimed at bringing mathematical knowledge from the experiential/work world to the classroom? The objective is to analyze how Mathematics teaching, supported by activities present in the daily lives of EJA students and brought by them into the classroom through videos, contributes to the understanding of scientific knowledge. To this end, we seek support in the specificities of Mathematics teaching focused on EJA, using short videos as a teaching resource. Vygotsky's historical-cultural perspective is adopted as a theoretical reference, bringing nuclear aspects such as Interaction, Concept Formation and Zone of Imminent Development. The research takes a qualitative approach and action research as characteristics, involving the production of data based on the records of the researcher who is the class teacher in his logbook, the activities and videos produced by the participants. The analysis of this material takes place based on categories given a priori, namely: 1) Rescue of spontaneous knowledge; 2) Construction of scientific concepts; 3) Application of mathematical concepts in experiential situations; and, 4) Assessment of the concepts covered in the didactic sequence. The results of the study point to the relevance of the didactic sequence developed as it relates mathematical knowledge from the experiential world with that discussed in the classroom, showing students that knowledge is connected and does not belong to different worlds. The reality perceived by the students based on the analysis of the videos produced by their colleagues and the explanations given by them, was another aspect that pointed to the viability of the proposal developed, as well as the participation and involvement of the class when their colleagues they established relationships between the Mathematics of their daily work and that present in textbooks. The educational product is linked to the production of a set of short videos that contextualize mathematical concepts in work activities, especially those carried out by the study subjects. The product is available on a website that can be accessed from the EduCapes Portal (http://educapes.capes.gov.br/handle/capes/742104) or through the program page (www.upf.br/ppgecm).